How does Financial Development and Economic Growth affect Energy Consumption;The Panel VAR Analysis of 5 Turk Countries - Volkan Han; Oğuz Öcal (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In this study, the linkage among energy consumption, financial development, foreign direct investments and economic growth in 5 Turk’s countries (Turkey, Azerbaijan, Kazakhstan, Kyrgyz Republic and Tajikistan) were examined during the 1992-2017 observation period. Panel var methodology was applied by using 3 different financial development indicators. According to analysis results, the increase in bank deposits, which is one of the financial development indicators, positively affects the energy demand, while the increase in private loans negatively affects the energy demand. On the other hand, energy consumption increases have a negative impact on financial development. When the economic growth and energy consumption relation are examined, the increase in energy consumption affects economic growth positively, foreign direct investment has an inverse relationship with energy consumption. The causality results suggest that there is two-way causality between energy consumption and all other variables except liquid liabilities, and there is one-way causality running from energy consumption to liquid liabilities. An increase in energy consumption, foreign direct investments and, liquid liabilities are the drivers of economic growth. However, although the increase in energy consumption has a positive effect on economic growth, it has a negative effect on financial development. Therefore, reducing foreign dependency and turning to renewable energy sources and energy-efficient technologies will reduce energy costs on the financial market and increase the welfare of the country in the long run.